Short-term exposure to high ambient air pollution increases airway inflammation and respiratory symptoms in chronic obstructive pulmonary disease patients in Beijing, China. (September 2016) - Wu, Shaowei; Ni, Yang; Li, Hongyu; Pan, Lu; Yang, Di; Baccarelli, Andrea A.; Deng, Furong; Chen, Yahong; Shima, Masayuki; Guo, Xinbiao
Abstract: Background: Few studies have investigated the short-term respiratory effects of ambient air pollution in chronic obstructive pulmonary disease (COPD) patients in the context of high pollution levels in Asian cities. Methods: A panel of 23 stable COPD patients was repeatedly measured for biomarkers of airway inflammation including exhaled nitric oxide (FeNO) and exhaled hydrogen sulfide (FeH2 S) (215 measurements) and recorded for daily respiratory symptoms (794 person-days) in two study periods in Beijing, China in January–September 2014. Daily ambient air pollution data were obtained from nearby central air-monitoring stations. Mixed-effects models were used to estimate the associations between exposures and health measurements with adjustment for potential confounders including temperature and relative humidity. Results: Increasing levels of air pollutants were associated with significant increases in both FeNO and FeH2 S. Interquartile range (IQR) increases in PM2.5 (76.5 μg/m 3, 5-day), PM10 (75.0 μg/m 3, 5-day) and SO2 (45.7 μg/m 3, 6-day) were associated with maximum increases in FeNO of 13.6% (95% CI: 4.8%, 23.2%), 9.2% (95% CI: 2.1%, 16.8%) and 34.2% (95% CI: 17.3%, 53.4%), respectively; and the same IQR increases in PM2.5 (6-day), PM10 (6-day) and SO2 (7-day) were associated with maximum increases in FeH2 S of 11.4% (95% CI: 4.6%, 18.6%), 7.8% (95% CI: 2.3%, 13.7%) and 18.1% (95% CI: 5.5%, 32.2%), respectively. Increasing levels of air pollutants were also associated with increased odds ratios of sore throat, cough, sputum, wheeze and dyspnea. Conclusions: FeH2 S may serve as a novel biomarker to detect adverse respiratory effects of air pollution. Our results provide potential important public health implications that ambient air pollution may pose risk to respiratory health in the context of high pollution levels in densely-populated cities in the developing world. Highlights: Few studies have investigated air pollution effects in COPD patients in China. Air pollution was associated with increased exhaled nitric oxide and hydrogen sulfide. Air pollution was also associated with increased odds ratios of respiratory symptoms. Exhaled hydrogen sulfide may serve as a novel marker to detect air pollution effects. Air pollution may pose risk to respiratory health in highly-polluted areas.